Message - Awotona, Prof Olanrewaju Rita-Marie (Universal Journal of Pharmaceutical Research, 2020)
Knowledge is the factory in which we are all workers in this season of the world crisis. Knowledge seems to have filled the earth, yet more knowledge is needed about our circumstances. We as a world are faced with the challenges of health as a matter of urgency and knowledge is still what will bring, an understanding of our situation, relief and ultimate mastery of those challenges. The dissemination of knowledge which has come from research far and wide and from many nations of the world is of utmost importance. Now more than ever UJPR is relevant. Never before has pharmaceutical research been more relevant. It seems the world is looking to the pharmaceuticals to salvage her. UJPR started just a few years ago, but it has taken giant strides since then. I remember the days when we were deciding the logo and format and design. Now it has become a pipe for necessary and important knowledge to be distributed to those needing it. The journal has scaled many hurdles and now indexed in many services, with many countries now participating. One of the unique features of UJPR which it must continue to nurture is the wholesomeness and interdisciplinary characteristics it has. Every field of pharmaceuticals is included and and this makes it a one stop platform of knowledge. The world is in turmoil now, yet many nations have taken knowledge from various journals and works of research and produced for themselves products that have brought relief to their people. There is no doubt in my mind that UJPR is going the right way and more encouragement should be given to younger researchers to be more innovative and be challenged to solve the problems of the times. Researchers at this time have the mandate to bring to the table of knowledge answers for this generation. The answers are all around us, but only journals such as UJPR will put it out in the marketplace for others to see and use to their benefit. I continue to congratulate all those who have published in this journal and those who have worked to make it an excellent journal, which is growing in stature by the day. We should look forward to more cutting edge research reports, especially in the areas of pharmaceuticals which include all the herbal medicines and nutraceuticals. Majority of the world are looking to natural sources to solve health issues. Apart from the hope of vaccines for new diseases, phytomedicines are a major hope too. I look forward to seeing more interesting works published in this journal as it has set itself a high standard. This standard must be maintained and improved upon. It will be the duty of all to keep publishing the journal and bringing it to the focus of other researchers around the world. It is also interesting to note that pharmaceutical now has attracted those of other professions and there is a collaboration and interdisciplinary move that’s bringing out unique and impressive medicines. Knowledge is on the increase and at a faster rate than ever, more so now that the world needs to coordinate its efforts. UJPR will have cause to explore greater avenues of reaching out to researchers to bring in what is needed to become more relevant, a source of greater international standard, ethically reliable and well scrutinized data. UJPR is going to greater heights and in next issues we are bound to see the excellent research. I congratulate UJPR and look forward to future issues as we contribute to the mountain of knowledge of the world.